2020
DOI: 10.1111/imm.13254
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative and qualitative alterations of circulating myeloid cells and plasmacytoid DC in SARS‐CoV‐2 infection

Abstract: SARS-CoV-2 is responsible for a new infectious disease (COVID-19) in which individuals can either remain asymptomatic or progress from mild to severe clinical conditions including acute respiratory distress syndrome and multiple organ failure. The immune mechanisms that potentially orchestrate the pathology in SARS-CoV-2 infection are complex and only partially understood. There is still paucity of data on the features of myeloid cells involved in this viral infection. For this reason, we investigated the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
73
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 22 publications
22
73
1
Order By: Relevance
“…We identified four additional articles specifically reporting on mHLA‐DR measurement at hospital admission (23–26). Patients presented with various levels of severity, and routine flow cytometry was performed and results were expressed as means of fluorescence intensities (for the total CD14+ monocyte population) meaning that results cannot be strictly compared between centers.…”
Section: Clinical Results In Covid‐19 Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified four additional articles specifically reporting on mHLA‐DR measurement at hospital admission (23–26). Patients presented with various levels of severity, and routine flow cytometry was performed and results were expressed as means of fluorescence intensities (for the total CD14+ monocyte population) meaning that results cannot be strictly compared between centers.…”
Section: Clinical Results In Covid‐19 Patientsmentioning
confidence: 99%
“…Moreover, Moratto et al also observed that, among severe patients, those who progressed to a critical status (admission to ICU) had the lowest expression (23). In addition, as mentioned above, in COVID-19 patients, the proportion of non-classical monocytes (CD14 low CD16+) was lower than in controls (23,25).…”
Section: Mhla-dr Measurement At Hospital Arrival (Various Severities)mentioning
confidence: 85%
See 1 more Smart Citation
“…The proportions of these three subsets in the circulation of healthy individuals are well defined, although an expansion of inflammatory monocytes has been described in autoimmunity and chronic inflammation. 82 Accumulating data have shown that proportions of monocyte subsets are altered in COVID-19, 83,84 together with a significant downregulation of monocyte HLA-DR expression. 83,85,86 In addition to monocytes, DCs are another innate cell population with a crucial role in nasal immunity.…”
Section: Mucosal and Systemic Immune Response To Sars-cov-2mentioning
confidence: 99%
“…82 Accumulating data have shown that proportions of monocyte subsets are altered in COVID-19, 83,84 together with a significant downregulation of monocyte HLA-DR expression. 83,85,86 In addition to monocytes, DCs are another innate cell population with a crucial role in nasal immunity. 87 Two subsets of DCs have been described: plasmacytoid DCs (pDCs), which rapidly respond to viral infections secreting high amounts of type I and III IFNs, and myeloid DC (mDC), which act as sentinels ready to stimulate T cells.…”
Section: Mucosal and Systemic Immune Response To Sars-cov-2mentioning
confidence: 99%